Process for hydrosilylation of alkenes in ionic liquids in preparation of alkylchlorosilanes. - Bauer, A.; Frey, T.; Wasserscheid, Peter; Schulz, Peter; Hofmann, Norbert (2008)
Alkylchlorosilanes were prepd. by hydrosilylation of alkenes R8R9C:CR10R11 (2; R8-R11 = H, optionally halo-, amino-, alkoxy-, cyano- of isocyanato-substituted C1-18 hydrocarbyl, Cl, F, C1-18 alkoxy) by silanes HaSiR4-a (1; R = H, optionally halo C1-18 hydrocarbyl, C1-18 alkoxy; a = 1-3), preferably by chlorosilanes RcHdSiCl4-c-d (3; same R, c = 0-4, d = 1-3), catalyzed by transition metal complexes, preferably by platinum complexes dissolved in ionic liqs. [A+][Y-] (4; Y- = BArF4-, BF4-, P(C2F5)3F3-, SbF6-, AsF6-, fluorosulfonate, carboxylate, sulfonate, organyl sulfate, diorganyl phosphate, disulfonylimidate; A+ = tetraorganylammonium, tetraorganylphosphonium, imidazolium, pyridinium, pyrazolium, triazolium, picolinium, pyrrolidinium), optionally supported by high-porous silica. In an example, the silica-supported catalyst was prepd. by adsorption of a soln. of 0.7 mg of PtCl4 in 1.0 g of 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imidate on 5 g of granulated silica (0.2-0.5 mm particles) followed by reaction of 6.3 g of allyl chloride with 11.7 g of trichlorosilane at 100°, giving (trichloropropyl)trichlorosilane with 70% yield and 73% selectivity. In another example, the catalytic soln. of PtCl4 in 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imidate was reused three times with any loss of catalytic activity. [on SciFinder(R)]
Keywords: hydrosilylation ionic liq allyl chloride chloropropylsilane prepn improved process; silane halosilane prepn improved process hydrosilylation ionic liq